Epidemiology of acute diarrhea caused by rotavirus in sentinel surveillance sites of Vietnam, 2012–2015. Issue 51 (14th December 2018) - Huyen, Dang Thi Thanh; Hong, Duong Thi; Trung, Nguyen Thanh; Hoa, Tran Thi Nguyen; Oanh, Nguyen Kieu; Thang, Ho Vinh; Thao, Nguyen Thi Thanh; Hung, Do Manh; Iijima, Makiko; Fox, Kimberley; Grabovac, Varja; Heffelfinger, James; et al.
Abstract: A prospective, multicentre study was conducted in four sentinel surveillance hospitals to assess the trend and epidemiology of acute diarrhea caused by Rotavirus in Vietnam. During the period 2012–2015, a total 8, 889 children under 5 years of age were enrolled in the surveillance, and 8689 stool samples were collected. Of these cases, Rotavirus was most common pathogen 46.7% (4054 cases); in which 26.6% (1117) rotavirus-positive stool samples were evaluated to identify genotypes. The proportion of rotavirus positive specimens decreased annually from 54.7% in 2012 to 36.6% in 2015. Rotavirus was detected year-round, but most rotavirus gastroenteritis cases (77.1%) occurred between December and May, corresponding to the rotavirus seasonality. It is found that the peaks varied by regions. Rotavirus positivities varied between the youngest and oldest age, but children 6–11 months old (38.8%) and 12–23 months old (38.4%) counted for most cases. A significant higher number of diarrhea within 24 hours (8.3 times, 95%CI: 8.1–8.4 times) and higher proportion of severe dehydration (12.9%) in Rotavirus positive group than that in Rotavirus negative group (7.7 times, 95%CI: 7.6–7.9 times; and 9.7%, respectively). A downtrend of prevalence of G1P[8] was observed from 82% in 2013 to 15% in 2015. However, G2P[4] was found in 5% of samples in 2012, 9% in 2013, 36% in 2014, and 28% in 2015. Rotavirus infection is the most important cause of acute diarrhea among hospitalized children in Vietnam, and a rotavirus vaccination program for children may significantly reduce this disease.